2015
DOI: 10.1038/bmt.2015.301
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells in allogeneic hematopoietic cell transplantation: benefit or burden?

Abstract: Plasmacytoid dendritic cells (pDCs) bridge innate and adaptive immune responses and have important roles in hematopoietic engraftment, GvHD and graft-versus-leukemia responses following allogeneic hematopoietic cell transplantation (HCT). In addition, pDCs mediate antiviral immunity, particularly as they are the body’s primary cellular source of type I interferon. Given their pleiotropic roles, pDCs have emerged as cells that critically impact transplant outcomes, including overall survival. In this article, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 134 publications
1
26
0
Order By: Relevance
“…In patients with systemic lupus erythematosus, it has been previously shown that plasmacytoid dendritic cells drive the differentiation of immature regulatory B cells, and that these interactions are normalized in patients responding to rituximab therapy [38]. After HCT, the increase in plasmacytoid dendritic cells in bone marrow allografts is associated with less cGVHD [39], and rituximab has been successfully used as salvage therapy for steroid refractory cGVHD [40].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with systemic lupus erythematosus, it has been previously shown that plasmacytoid dendritic cells drive the differentiation of immature regulatory B cells, and that these interactions are normalized in patients responding to rituximab therapy [38]. After HCT, the increase in plasmacytoid dendritic cells in bone marrow allografts is associated with less cGVHD [39], and rituximab has been successfully used as salvage therapy for steroid refractory cGVHD [40].…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of pDCs in inducing aGVHD is interesting, but so far these cells have not been studied extensively in this context (26, 51). pDCs constitute a multifunctional cell type involved e.g., in production of type-I interferons against virus infections, induction of Th17 cell response, and presentation of peptide antigens by MHC class II to T cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…Then, they may become activated and act as APC. However, experimental data for this is still scarce (51, 53). Peric et al recently reported that high levels of pDCs post-HSCT predicted good clinical outcome with less severe GVHD and better overall survival (53).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a phase I clinical trial, we recently demonstrated that 6 weeks course of subcutaneous injection of FLT3 ligand after autologous HCT increased the frequency of blood CD11c+ pDC precursors 5-fold without affecting other mature cell lineages [36]. Furthermore, high pDC can recruit NK and T cells to further promote local and systemic immune responses [37], yet our data did not confirm their correlation in peripheral blood.…”
Section: Discussionmentioning
confidence: 61%